Systematic revision of the family Pleioplanidae Faubel, 1983 (Polycladida, Acotylea): New genus and combinations - Rodríguez, Jorge (2017)
New morphological information, reconsiderations and the first combination of a generic name based on a previously established species are presented in the current revision of the family Pleioplanidae (Polycladida, Acotylea). Species belonging to this family are briefly presented and Laqueusplana bocki gen. et sp. nov. is described. An identification key to all valid species of Pleioplanidae is provided. Furthermore, results from phylogenetic analyses of the species treated herein are discussed.